Depression Subscale of the Hospital Anxiety and Depression Scale applied preoperatively in spinal surgery - Falavigna,Asdrubal (2012)
OBJECTIVE: To evaluate the accuracy of the Depression Subscale of Hospital Anxiety and Depression Scale (HADS-D) in spine surgery, comparing it to Beck Depression Inventory (BDI). METHODS: In a cross-sectional study, the HADS-D and the BDI were applied to patients undergoing spine surgery for lumbar (n=139) or cervical spondylosis (n=17). Spearman correlation tests for HADS-D and BDI were applied. The internal consistency of HADS-D was estimated by Cronbach's alpha coefficient. RESULTS: According to the BDI, the prevalence of depression was of 28.8% (n=45). The Spearman r coefficient between HADS-D and BDI was 0.714 (p<0.001). Cronbach's alpha for HADS-D was 0.795. The area of the ROC curve was 0.845. Using a cutoff for HADS-D >10, there was a sensitivity of 71.1%, specificity of 95.4%, and positive likelihood-ratio of 15.78. CONCLUSIONS: HADS-D showed a strong correlation with BDI and good reliability. HADS-D is a good alternative for screening depression and assessing its severity.